2001
DOI: 10.2307/3583432
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Prenatal Care and Subsequent Modern Contraceptive Use in Bolivia, Egypt and Thailand

Abstract: Determinants of modern contraceptive use are usually examined in isolation of the effect of exposure to other aspects of health care systems. Maternal interaction with organised health service provision during post-conception and postpartum stages of reproduction can provide an opportunity to transfer contraceptive service information and counselling. We found that living in a community in which women have widespread health service contact is related to both prenatal care use and subsequent modern contraceptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
34
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 4 publications
6
34
1
Order By: Relevance
“…The argument was that the utilization of these services contributes to women's faith in the health systems and their contentment with the health care services, making them more likely to utilize the family planning services. This finding is in contrast with the study conducted in Thailand, which reported that the women who had utilized ANC did not necessarily adopt contraceptives after having index birth (Zerai & Tsui, 2001). However, similar to our finding, research in Mexico, Kenya, Indonesia, the Dominican Republic, and Peru found that the women who delivered in government or private health facilities were more likely to use postpartum contraceptive methods than those who delivered at home (Barber, 2007;Gebreselassie, Rutstein, & Mishra, 2008).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The argument was that the utilization of these services contributes to women's faith in the health systems and their contentment with the health care services, making them more likely to utilize the family planning services. This finding is in contrast with the study conducted in Thailand, which reported that the women who had utilized ANC did not necessarily adopt contraceptives after having index birth (Zerai & Tsui, 2001). However, similar to our finding, research in Mexico, Kenya, Indonesia, the Dominican Republic, and Peru found that the women who delivered in government or private health facilities were more likely to use postpartum contraceptive methods than those who delivered at home (Barber, 2007;Gebreselassie, Rutstein, & Mishra, 2008).…”
Section: Discussioncontrasting
confidence: 85%
“…Moreover, literature suggests that though the integration of MCH and FP services has come to focus following the International Conference on Population and Development in Cairo (Hardee & Yount, 1995), only a few papers based on some developing countries have tested the linkages between utilization of MCH services and contraceptive use (Hotchkiss et al, 1999;Seiber et al, 2005;Zerai & Tsui, 2001).…”
Section: Research-article20172017mentioning
confidence: 99%
“…The factors contributing to postpartum contraceptive use have been studied previously and include socio-demographic factors, prior experiences, obstetric care service utilisation, and antenatal-postnatal education [16][17][18][19][20][21][22][23][24][25][26][27]. The differences in the time and type of educational interventions and the heterogeneity of the population have yielded diverse outcomes [16][17][18][19][20].…”
mentioning
confidence: 99%
“…Prior study performed by Zerai et al, investigated the role of prenatal care for modern contraceptive use in Bolivia, Egypt and Thailand. They suggested that prenatal care strongly affects subsequent modern method use [21]. The data from the Demographic and Health Survey (DHS) in Kenya showed that ANC service intensity and previous method use were related to postpartum contraception [22].…”
mentioning
confidence: 99%
See 1 more Smart Citation